EXTH-65. BET INHIBITION IN COMBINATION WITH TEMOZOLOMIDE TARGETS MYCN-POSITIVE GLIOBLASTOMA CELLS. (5th November 2018) - Čančer, Matko; Drews, Lisa; Rosén, Gabriela; Westermark, Bengt; Nelander, Sven; Forsberg-Nilsson, Karin; Uhrbom, Lene; Weishaupt, Holger; Swartling, Fredrik
Abstract: Glioblastoma (GBM) is the most common malignant brain tumor in adults with a 15 month median survival after diagnosis. Patients receive surgical resection of the tumor, followed by aggressive radio- and chemotherapy with temozolomide (TMZ). Many human cancers including GBM demonstrate addiction to MYC transcription factor signaling and thus become susceptible to inhibition of MYC downstream genes. JQ1 is an effective inhibitor of BET Bromodomains, a class of epigenetic readers regulating expression of MYC genes and their downstream targets. In a panel of 19 patient-derived GBM cell lines, we showed that BET inhibition alone and in combination with TMZ decreases viability by inducing cell cycle arrest, apoptosis and senescence. We propose a distinct expression signature of GBM cells that correlates with a sensitivity to BET inhibition. Cell lines most sensitive to BET inhibition exhibited ten-fold upregulation of MYCN, as compared to resistant cell lines, while we could not find a correlation between MYC expression and sensitivity to the inhibition. Following BET inhibition, JQ1-sensitive cells downregulated MYCN both on mRNA and protein level, while the inhibition of JQ1-resistant cells had no effect on MYCN expression. In JQ1-sensitive cells, we found enrichment of pathways regulating cell cycle, DNA replication, DNA damage response and repair. As DNA repair leads to an acquired chemoresistance to TMZ, JQ1 treatment in combination with TMZ can further inhibit proliferation of TMZ-resistant cells. Intriguingly, JQ1-sensitive cells expressed high levels of OLIG2 and LGR5, suggesting that BET inhibition targets a subset of proneural GBM progenitors. Taken together, we suggest that BET inhibition can increase the potency of TMZ therapy in particular for GBM patients with a MYCN-positive signature. Ongoing in vivo evaluation of JQ1 and TMZ aims to determine the efficacy of the drug combination in inhibiting tumor growth.